Remote ischemic preconditioning as treatment for non-ischemic gastrointestinal disorders: beyond ischemia-reperfusion injury - Camara Lemarroy, Carlos Rodrigo (WJG Press, 2014)
Common gastrointestinal diseases such as radiation enteritis (RE), acute pancreatitis, inflammatory bowel diseases (IBD) and drug-induced hepatotoxicity share pathophysiological mechanisms at the molecular level, mostly involving the activation of many pathways of the immune response, ultimately leading to tissue injury. Increased oxidative stress, inflammatory cytokine release, inflammatory cell infiltration and activation and the up-regulation of inflammatory transcription factors participate in the pathophysiology of these complex entities. Treatment varies in each specific disease, but at least in the cases of RE and IBD immunosuppressors are effective. However, full therapeutic responses are not always achieved. The pathophysiology of ischemiareperfusion (IR) injury shares many of these mechanisms. Brief and repetitive periods of ischemia in an organ or limb have been shown to protect against subsequent major IR injury in distant organs, a phenomenon called remote ischemic preconditioning (RIP). This procedure has been shown to protect the gut, pancreas and liver by modulating many of the same inflammatory mechanisms. Since RIP is safe and tolerable, and has shown to be effective in some recent clinical trials, I suggest that RIP could be used as a physiologically relevant adjunct treatment for non-ischemic gastrointestinal inflammatory conditions.